1985
DOI: 10.1190/1.1441933
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between compressional‐wave and shear‐wave velocities in clastic silicate rocks

Abstract: New velocity data in addition to literature data derived from sonic log, seismic, and laboratory measurements are analyzed for elastic silicate rocks. These data demonstrate simple systematic relationships between compressional and shear wave velocities. For water-saturated elastic silicate rocks, shear wave velocity is approximately linearly related to compressional wave velocity and the compressional-to-shear velocity ratio decreases with increasing compressional velocity. Laboratory data for dry sandstones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
582
5
10

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,347 publications
(630 citation statements)
references
References 23 publications
33
582
5
10
Order By: Relevance
“…However, we showed in Section 3.2 that the coherence between horizontal and vertical ground motion is in accordance with the propagation of Rayleigh waves and a velocity of 300 m s −1 is in agreement with shear wave energy propagating in unconsolidated saturated sediments ( Castagna et al 1985;Vernon et al 1998). At the Ketzin site Xu et al (2012) found shear wave velocities of 303.6 m s −1 in the shallowest 5 m.…”
Section: Analysis Of the Dominating Phase In The Cross-correlationssupporting
confidence: 59%
“…However, we showed in Section 3.2 that the coherence between horizontal and vertical ground motion is in accordance with the propagation of Rayleigh waves and a velocity of 300 m s −1 is in agreement with shear wave energy propagating in unconsolidated saturated sediments ( Castagna et al 1985;Vernon et al 1998). At the Ketzin site Xu et al (2012) found shear wave velocities of 303.6 m s −1 in the shallowest 5 m.…”
Section: Analysis Of the Dominating Phase In The Cross-correlationssupporting
confidence: 59%
“…This work shows that there is a linear relationship between P-wave velocity and S-wave velocity for brine saturation. In the Gulf of Mexico, Castagna [18] established the Mudrock Line to be Vp = 1.16Vs + 1.36 for velocity in km/s. From Figure 19 Mudrock Line for the study area is here established to be: V p = 0.807V s + 1.600 (14) where velocity is in km/s.…”
Section: Resultsmentioning
confidence: 99%
“…9) amplitude-dependent section. The S-wave velocity section is calculated with the formula of Castagna et al (1985). The pseudo-Poisson reflectivity shows the normalised change in pseudo-Poisson ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Amplitude versus offset inversions using the Aki and Richards linearised approximation of the Zoeppritz equation yield the following attribute sections: Pwave reflectivity section (DV P /V P ), S-wave reflectivity section (DV S /V S ), as a lithology indicator of their linear combinations being the pseudo Poisson reflectivity (Dh/ h = DV P /V P -D V S /V S ), and the Fluid Factor. The Fluid Factor, a hydrocarbon indicator, is a deviation from the ''mudrock line'' of Castagna et al (1985) that gives a relation of P-wave velocity to S-wave velocity for water-saturated clastic silicate rocks. The Fluid Factor is given as…”
Section: Principles Of Avo Analysismentioning
confidence: 99%
See 1 more Smart Citation